Markers for toxicity to HepG2 exposed to cadmium sulphide quantum dots; damage to mitochondria. (30th December 2016) - Paesano, Laura; Perotti, Alessio; Buschini, Annamaria; Carubbi, Cecilia; Marmiroli, Marta; Maestri, Elena; Iannotta, Salvatore; Marmiroli, Nelson
Abstract: Interaction of living organisms with quantum dots (QDs) is certainly more focused on environment and occupational exposure associated with production and release or disposal. Here, the transcription of genes involved in mitochondrial organization and function in HepG2 cells exposed to cadmium sulphide (CdS) QDs has been profiled to highlight biomarkers of exposure and effect to be tested for other cadmium based QDs. At low concentrations, exposure to CdS QDs induced only minor damage to nuclear DNA, and none to mitochondrial DNA. However, the stress caused an increase in the production of reactive oxygen species (ROS), which triggered the mitochondria-mediated intrinsic apoptotic pathway involving a cascade of transcriptomic events, finally prompting the activation of a rescue pathway. The transcriptomic analysis confirmed the involvement in the response to CdS QDs of genes related to apoptosis ( AIFM2 and APAF1 ), oxidative stress response ( OXR1 and AOX1 ) and autophagy ( ATG3 and ATG7 ), as potential biomarkers. Other possible biomarkers specific for mitochondria function were LONP1 and HSPD1 .